2001
DOI: 10.1016/s0735-1097(01)01595-9
|View full text |Cite
|
Sign up to set email alerts
|

Carotid angioplasty and stenting versus carotid endarterectomy: randomized trial in a community hospital

Abstract: Carotid stenting is equivalent to CEA in reducing carotid stenosis without increased risk for major complications of death/stroke. Because of shortened hospitalization and convalescence, CAS challenges CEA as the preferred treatment of symptomatic carotid stenosis if a reduction in costs can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
230
2
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(246 citation statements)
references
References 45 publications
7
230
2
7
Order By: Relevance
“…Em contraste a esses dois estudos, um estudo realizado em um único centro nos EUA randomizou 104 pacientes com estenose sintomá-tica > 70%, e não houve AVC tanto no grupo cirúrgico quanto no endovascular, ocorrendo um óbito na endarterectomia e nenhum no grupo do stent 8 .…”
Section: Discussionunclassified
“…Em contraste a esses dois estudos, um estudo realizado em um único centro nos EUA randomizou 104 pacientes com estenose sintomá-tica > 70%, e não houve AVC tanto no grupo cirúrgico quanto no endovascular, ocorrendo um óbito na endarterectomia e nenhum no grupo do stent 8 .…”
Section: Discussionunclassified
“…However, so far there has been no evidence of CAS superiority over CEA. [6][7][8][9][10][11][12][13] In Brazil, practice of carotid surgery has more than 40 years, and a survey has been published about indications and about who would indicate that procedure: neurologists, cardiologists or vascular surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…29 A small single-institution study randomized over 100 patients with symptomatic carotid stenosis to CAS or CEA and found equivalent and very low rates of complications in either arm. 30 A follow-up randomized trial of over 80 asymptomatic patients demonstrated similarly equivalent very low rates of complications in either arm. 31 The largest study so far (CAVATAS) 32 consisted mainly of carotid balloon angioplasty (74%) with a small number of implanted stents and randomized over 500 patients to CEA or endovascular therapy.…”
Section: Early Randomized Studiesmentioning
confidence: 91%